Giorgio Vasari als overgangsfiguur? - van Veen , Henk Th. (Incontri. Rivista europea di studi italiani, 2023)
Bespreking van: Laura Overpelt, ‘By a Single Painter’. The Organization and Representation of Giorgio Vasari’s Decorative Projects in the Palazzo Vecchio. Dissertatie Open Universiteit, 2022, 2 vols, 464 en 428 p., ISBN 9789464217063.